Fuzzy Control of a Germination Chamber - Marinelli, Marcelo (2017)
The design of a fuzzy control system for a germination chamber for hydroponic crops is presented. The system measures humidity and temperature inside the chamber and, by means of a Sugeno type fuzzy controller embedded in an Arduino board, it generates control signals that are sent to a forced ventilation system and to the artificial lighting control system. Experiences were carried out with a germination chamber using this fuzzy control system. Lettuce seeds were sowed in the fuzzy control chamber and on a conventional culture tray, with the former yielding better growth results.